2017
DOI: 10.3390/ijerph14020154
|View full text |Cite
|
Sign up to set email alerts
|

Mosquitocidal Activity and Mode of Action of the Isoxazoline Fluralaner

Abstract: Mosquitoes, such as Aedes aegypti and Anopheles gambiae, are important vectors of human diseases. Fluralaner, a recently introduced parasiticide, was evaluated as a mosquitocide in this study. On Ae. aegypti and An. gambiae fourth-instar larvae, fluralaner had 24-h LC50 (lethal concentration for 50% mortality) values of 1.8 ppb and 0.4 ppb, respectively. Following topical application to adult Ae. aegypti, fluralaner toxicity reached a plateau in about 3 days, with 1- and 3-day LD50 (lethal dose for 50% mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 23 publications
1
32
0
2
Order By: Relevance
“…The caveat to this first-instar bioassay was that these small larvae were more susceptible to xenobiotics and may not provide an accurate prediction of mortality for later instars or adults. This effect was recently highlighted by comparing the toxicity of fluralaner to Aedes aegypti mosquito larvae [23]. Fluralaner’s toxicity to Ae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The caveat to this first-instar bioassay was that these small larvae were more susceptible to xenobiotics and may not provide an accurate prediction of mortality for later instars or adults. This effect was recently highlighted by comparing the toxicity of fluralaner to Aedes aegypti mosquito larvae [23]. Fluralaner’s toxicity to Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Fluralaner’s toxicity to Ae. aegypti fourth-instar larvae was found to be 1.8 ppb [23]; however, a previous study reported greater than 90% mortality to first instar Ae. Aegypti larvae at 1.2 ppt [24], a greater than 1500-fold difference in toxicity between the two life stages.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological recordings from the larval central nervous system (CNS) were performed essentially as previously described. 25 The CNS was dissected in physiological saline containing (M) NaCl (0.157), KCl (0.003), CaCl 2 (0.002) and HEPES (0.004), at pH 7.2, and transected posterior to the cerebral lobes to eliminate the blood–brain barrier and facilitate penetration of chemicals into the CNS. A recording glass pipette suction electrode was used to monitor descending spike activity from several peripheral nerve trunks.…”
Section: Methodsmentioning
confidence: 99%
“…Isoxazolines are potent inhibitors of gamma-aminobutyric acid (GABA)- and glutamate-gated chloride channels in the nervous system of invertebrates [3]. Thereby, they result in uncontrolled neural activity and finally death of insects and acarines [4]. Binding to and blocking of phylogenetically related vertebrate pentameric ligand-gated chloride channels (i.e.…”
Section: Introductionmentioning
confidence: 99%